Efficacy and safety of lesogaberan in gastro-oesophageal reflux disease: a randomised controlled trial. Issue 9 (23rd June 2012) - Shaheen, Nicholas J; Denison, Hans; Björck, Karin; Karlsson, Maria; Silberg, Debra G
Abstract : Objective: Lesogaberan (AZD3355) is a novel γ-aminobutyric acid B-type receptor agonist designed to treat gastro-oesophageal reflux disease (GERD) by inhibiting transient lower oesophageal sphincter relaxations. A randomised, double-blind, placebo-controlled, multi-centre phase IIb study was performed to assess the efficacy and safety of lesogaberan as an add-on to proton pump inhibitor (PPI) therapy in patients with GERD who are partially responsive to PPI therapy (ClinicalTrials.gov reference: NCT01005251 ). Design: In total, 661 patients were randomised to receive 4 weeks of placebo or 60, 120, 180 or 240 mg of lesogaberan twice daily, in addition to ongoing PPI therapy. Symptoms were measured using the Reflux Symptom Questionnaire electronic Diary. Response to treatment was defined as having an average of ≥3 additional days per week of not more than mild GERD symptoms during treatment compared with baseline. Results: In the primary analysis, 20.9%, 25.6%, 23.5% and 26.2% of patients responded to the 60, 120, 180 and 240 mg twice daily lesogaberan doses, respectively, and 17.9% responded to placebo. The response to the 240 mg twice daily dose was statistically significantly greater than the response to placebo using a one-sided test at the predefined significance level of p<0.1. However, the absolute increases in the proportions of patients who responded to lesogaberan compared with placebo were low. Lesogaberan was generally well tolerated, although six patients receiving lesogaberan developed reversible elevated alanine transaminase levels. Conclusions: In patients with GERD symptoms partially responsive to PPI therapy, lesogaberan was only marginally superior to placebo in achieving an improvement in symptoms.